2020
DOI: 10.1210/clinem/dgaa776
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Thermal Ablation for Solitary T1bN0M0 Papillary Thyroid Carcinoma: A Multicenter Study

Abstract: Background Ultrasound guided thermal ablation plays an important role in the management of thyroid disease. The objective of this study was to evaluate the feasibility, efficacy, and safety of thermal ablation for patients with solitary T1bN0M0 PTC who are ineligible for or unwilling to undergo surgery. Materials and Methods Data pertaining to 172 patients (38 males and 134 females) who received thermal ablation therapy at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…A large cohort study with a mean follow-up of 42.15 months [14] has reported the efficacy of RFA in the treatment of PTMC with a mean VRR of 98.8%, and tumor disappearance rate of 88.41%. In addition, a multicenter study [23] on thermal ablation for the treatment of T1bN0M0 PTC showed a VRR of 99% at 48-month visit, and complete disappearance rate of 61.6% during a mean follow-up of 24.9 months. In the present study, the mean VRR at last follow-up (93.7%) was similar to those previous studies, but the disappearance rate (16.7%) was much lower.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A large cohort study with a mean follow-up of 42.15 months [14] has reported the efficacy of RFA in the treatment of PTMC with a mean VRR of 98.8%, and tumor disappearance rate of 88.41%. In addition, a multicenter study [23] on thermal ablation for the treatment of T1bN0M0 PTC showed a VRR of 99% at 48-month visit, and complete disappearance rate of 61.6% during a mean follow-up of 24.9 months. In the present study, the mean VRR at last follow-up (93.7%) was similar to those previous studies, but the disappearance rate (16.7%) was much lower.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, US-guided thermal ablation has been introduced to treat low risk PTC [17,22,23], and obtained excellent results. A large cohort study with a mean follow-up of 42.15 months [14] has reported the efficacy of RFA in the treatment of PTMC with a mean VRR of 98.8%, and tumor disappearance rate of 88.41%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ablation guidelines and consensus statements indicate that thermal ablation can be used in benign and selected malignant thyroid nodules [6][7][8][9][10]. For instance, microwave ablation (MWA), radiofrequency ablation (RFA), or laser ablation were introduced to treat low-risk T1a papillary thyroid carcinoma [11,12], and even T1b [13]. However, most of these studies were single-center studies with relatively small number of patients, and the results were sometimes inconsistent [14].…”
Section: Introductionmentioning
confidence: 99%
“…RFA is characterized by its technical ease and non-invasive nature. To date, several leading institutes have reported successful outcomes with the use of RFA in the treatment of T1N0M0 PTC, recurrent thyroid cancers, and lymph node metastatic tumors (17)(18)(19)(20)(21)(22). As compared to SR, RFA is associated with comparable long-term outcomes, shorter hospital stay, and fewer temporary and permanent complications (23,24).…”
Section: Introductionmentioning
confidence: 99%